Reconstruction of Small Soft Tissue Nasal Defects - Wolfswinkel, Erik M.; Weathers, William M.; Cheng, David; Thornton, James F. (Seminars in Plastic Surgery, 2013)
Nasal defect repair has been one of the more challenging areas of reconstructive surgery due to the lack of uniform nasal skin thickness and complex contours. Currently, algorithms for medium to large nasal soft tissue defects have been well defined by various authors. Small defects, arbitrarily defined as 1 cm or less, still present significant challenges. In this article, the authors examine the options available to repair small soft tissue nasal defects and the appropriate situations in which each method is best suited.
Keywords: nasal reconstruction; Mohs surgery; small tissue defects